2002
DOI: 10.1046/j.1523-1755.2002.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products and mortality in hemodialysis patients

Abstract: In contrast to in vitro data and to current hypotheses, the presence of high serum AGEs, as measured by AGE-fl and CML, were not linked to increased mortality. Statistically, high serum AGEs partly overcame the negative impact of the acute phase response on mortality in hemodialysis patients. Whether the benefit of high serum AGEs is an epiphenomenon or reflects a better nutritional support needs further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
138
8
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(161 citation statements)
references
References 33 publications
11
138
8
4
Order By: Relevance
“…Previous studies in which AGE levels were estimated in plasma have reported ambiguous results regarding the association between AGE levels and mortality 35, 36. Conversely, the results of this meta‐analysis show that SAF is consistently associated with mortality.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies in which AGE levels were estimated in plasma have reported ambiguous results regarding the association between AGE levels and mortality 35, 36. Conversely, the results of this meta‐analysis show that SAF is consistently associated with mortality.…”
Section: Discussioncontrasting
confidence: 53%
“…Poor glycemic control might result directly in macrovascular complications, possibly secondary to the generation of advanced glycation end products (AGEs), and hence shorten survival of these patients. However, higher AGE levels in 312 hemodialysis patients were found to be paradoxically associated with better survival (30). Whether the benefit of high serum AGEs in these types of observational studies is an epiphenomenon or reflects a better nutritional status needs further study.…”
Section: Discussionmentioning
confidence: 97%
“…Schwedler et al (36) and Busch et al (37) reported that circulating AGE do not predict mortality in HD patients. However, serum AGE may be influenced by dialysis modalities, absorption from food, and smoking (38 -40).…”
Section: Discussionmentioning
confidence: 99%